2021
DOI: 10.1093/jipm/pmab009
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Boll Weevil (Coleoptera: Curculionidae) in the Colombian Caribbean: A Conceptual Model

Abstract: The boll weevil [BW; Anthonomus grandis grandis Boheman (Coleoptera: Curculionidae)] is the main pest in the cotton-producing regions throughout the Americas from Southern Texas to Argentina. In the Colombian Caribbean, frequent population outbreaks have resulted in cotton planting bans in some localities and in massive applications of insecticides elsewhere (up to 15 insecticide sprays per cotton season). To date, information on boll weevil management strategies in Colombia is only available in the forms of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
0
0
1
Order By: Relevance
“…Similarly, cotton mealybugs have been reported in more than 26 countries in various ecological zones [72]. Boll weevils have been reported throughout southern Texas to Argentina [73]. Several studies have indicated a tremendous increase in serious destructive pests within the cotton ecosystem.…”
Section: Urgent Need For Iot Towards Worldwide Major Cotton Pestsmentioning
confidence: 99%
“…Similarly, cotton mealybugs have been reported in more than 26 countries in various ecological zones [72]. Boll weevils have been reported throughout southern Texas to Argentina [73]. Several studies have indicated a tremendous increase in serious destructive pests within the cotton ecosystem.…”
Section: Urgent Need For Iot Towards Worldwide Major Cotton Pestsmentioning
confidence: 99%
“…Estos horizontes son escalas espacio-temporales que definen el escenario donde las acciones y los efectos de las acciones de una decisión tomarán lugar (la representación dimensional del sistema o problema de decisión). Las de políticas públicas y regulaciones son las de mayor efecto temporal y espacial, seguidas por las estratégicas, tácticas y operacionales (Burbano-Figueroa et al, 2021;Conway, 1984;Lum, 2015;Rabbinge et al, 1993;Webb, 2019). Las decisiones estratégicas presentan una escala temporal de años, las tácticas afectan semanas y las operacionales corresponden a días.…”
Section: ¿Cómo Implementar El Análisis De Decisiones?unclassified